Practices and Policies Around Wellness: Insights From the Internet Crimes Against Children Task Force Network - Mitchell, Kimberly J.; Gewirtz-Meydan, Ateret; O'Brien, Jennifer; Finkelhor, David (Frontiers in Psychiatry, 2022)
This article aims to understand what practices and training Internet Crimes Against Children (ICAC) Task Forces and affiliated agencies are currently using to help mitigate distress and promote wellbeing among investigators of child sexual abuse material (CSAM). Data were collected via telephone interviews with Commanders of 54 ICAC Task Forces as well as an online survey of 155 investigators at ICAC-affiliated agencies. Sixty-two percent of respondents said their agency had an Officer Wellness Program. Findings highlighted considerable gaps in protective practices with 46.1% of respondents mentioning the need for more wellness resources in their agency for personnel who have viewed CSAM as a high priority. Stigma created by help-seeking was the most widely acknowledged barrier discussed in relation to police wellness. A large and salient problem was the persistent lack of wellness practices in the affiliated agencies in comparison to the Task Forces themselves. Exposure to CSAM can be a source of stress for personnel and the results indicate concern about the problem and a diffusion of proactive initiatives, but barriers and inconsistent adoption remain.